ORAL TELANGIECTATIC GRANULOMA. CASE SERIES PRESENTATION - Ricardo, Jonathan Harris; López-Álvarez, Ary; Romero-Gómez, Kery (Revista Facultad de Odontología Universidad de Antioquia, 2012)
Telangiectatic granuloma is a benign hyperplastic lesion that results from trauma or local irritation. When it is present in the oral cavity, it appears as a fast growing red tumor with spontaneous bleeding, and it occurs more frequently in the vestibular gingiva of the maxillary anterior region. It`s a common pathology in South America, with cases in Argentina, Brazil, Chile, and Colombia. It is important for dentists to know its etiological factors, as well as the clinical and histological features for correct diagnosis and proper treatment. A series of four cases with diagnosis of telangiectatic granuloma is reported in this article.